2012
DOI: 10.4103/1947-2714.95897
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Gallbladder Polyps

Abstract: Gallbladder cancer is a rather uncommon disease, when it gives symptoms it has usually reached an incurable stage. Therefore, every attempt must be made to find the asymptomatic stages and look for premalignant gallbladder polyps. Even if gallbladder cancer is a rare disease, gallbladder polyps are common, only a few polyps develop to cancer. This makes gallbladder polyps another problem: which are the polyps that must be surgically removed, which shall be followed-up, or for how long? The author used the keyw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(165 citation statements)
references
References 31 publications
4
140
0
10
Order By: Relevance
“…Although most polyps are benign in nature, some early carcinomas show a similar appearance to benign polyps. Sonography has been used extensively in the pre-operative management of polyps, but this technique is generally not sufficient to differentiate between benign and malignant polyps, with the exception of advanced gallbladder cancer [18,19]. On the other hand, the overall prognosis for gallbladder cancer is extremely poor, with less than a 10% 5-year survival rate [6,20].…”
Section: Discussionmentioning
confidence: 99%
“…Although most polyps are benign in nature, some early carcinomas show a similar appearance to benign polyps. Sonography has been used extensively in the pre-operative management of polyps, but this technique is generally not sufficient to differentiate between benign and malignant polyps, with the exception of advanced gallbladder cancer [18,19]. On the other hand, the overall prognosis for gallbladder cancer is extremely poor, with less than a 10% 5-year survival rate [6,20].…”
Section: Discussionmentioning
confidence: 99%
“…Adenomyomatosis of the gallbladder (GA) remains a common entity among benign gallbladder masses, diagnosed in 2-8% of all cholecystectomies in recent studies. The differentiation of GA from gallbladder cancer is still required because of the similarity in the appearance between gallbladder adenomyomatosis and gallbladder cancer, although many studies have reported imaging findings of adenomyomatosis of the gallbladder using US, computed tomography (CT), magnetic resonance imaging (MRI) and EUS [15,18,19].…”
Section: Adenomyomatosesmentioning
confidence: 99%
“…The total EUS score on the basis of coefficient of multivariate analysis has been shown as follows: (maximum diameter in mm) + (internal echo pattern score; where heterogeneous = 4, homogeneous = 0) + (hyperechoic spot score; where presence = − 5, absence = 0). According to EUS scoring system, the specificity, sensitivity, and accuracy for the risk of malignant gallbladder polyps with scores of 12 or higher were reported for 83, 78, and 83%, respectively [4,15]. Proposed algorithm for management of gallbladder polyps is shown in Figure 4.…”
Section: Gallbladder Carcinomamentioning
confidence: 99%
See 2 more Smart Citations